Autobiography of Charles W. Squires - Squires, Charles W. (Charles Winder), 1841-1900.
Autobiography entitled, "The Last of Lee's Battle Line," chiefly relating to Squires's experiences as a Confederate army officer serving in Maryland, Gettysburg, Pa., Petersburg and Richmond, Va., Louisiana, and elsewhere, and his service after the Civil War in the Missouri National Guard.
Typewritten transcript.
Confederate army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Confederate States of America. -- Army -- Officers; Missouri. -- National Guard; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Louisiana -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Civil War, 1861-1865.; Richmond (Va.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; Virginia -- History -- Civil War, 1861-1865.; Army officers, Confederate